The impact of far-right political orientation and cultural values on conservative attitudes toward life and death in Europe: a multilevel approach - Ramos, Alice; Pereira, Cícero Roberto; Soboleva, Natalia; Vaitonytė, Meda (Frontiers in Political Science, 2024)
Belief systems are core organizing factors of social attitudes and behaviors, and their study has highlighted the role of conservatism as a contributing mechanism in mitigating concerns associated with change avoidance, as well as the reduction of uncertainty and ambiguity in life. Moreover, these aspects seem to be consistently used as powerful tools in the political and social discourse of the far-right. Life and death ethics are an example of issues that deal with the need for stability and control over personal and social life that people endorsing conservative values seek to attain. There is a rich line of studies on the individual and social explanatory factors of political conservatism, but less attention has been dedicated to moral conservatism as an autonomous and meaningful concept. The current research follows a multilevel approach to disentangle the individual and contextual correlates of conservative attitudes toward life and death. Thus, besides looking at the influence of individual choices related to religion and political orientation, this study also seeks to analyse the impact of the context, introducing in the model variables measuring economic performance, social and gender inequality, religious diversity and the prevalence of materialism and post-materialism values. Multilevel models using data from the 34 countries that participated in the last wave of the European Values Study (2017–2020), revealed an association between far-right orientation and conservative attitudes toward life and death, and that this relationship is moderated by materialism/post-materialism values, economic performance, and social inequality. Our findings reinforce the role of democracy as an environment where freedom of choice and thought are indisputable rights, cherished by most of the populations, regardless of their political position or their stance on moral issues.